2021
DOI: 10.1186/s12868-021-00675-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of open vs. closed skill exercise on the acute and chronic BDNF, IGF-1 and IL-6 response in older healthy adults

Abstract: Background Accumulating evidence shows that physical exercise has a positive effect on the release of neurotrophic factors and myokines. However, evidence regarding the optimal type of physical exercise for these release is still lacking. The aim of this study was to assess the acute and chronic effects of open-skill exercise (OSE) compared to closed-skill exercise (CSE) on serum and plasma levels of brain derived neurotrophic factor (BDNFS, BDNFP), and serum levels of insulin like growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 145 publications
1
21
0
Order By: Relevance
“…Regarding IL-6, our results indicate that the change of IL-6 concentration in blood serum increased in both intervention groups, whereas only changes from the MCI group became statistically significant. Consistent with the results of our study, Behrendt et al showed that both open and closed skill exercises were equally efficient in acutely increasing the IL-6 serum levels in healthy older adults (Behrendt et al, 2021 ). However, Forti et al ( 2014 ) showed results, contrary to ours, that IL-6 levels significantly decreased after 12 weeks of strength training in 20 older adults.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding IL-6, our results indicate that the change of IL-6 concentration in blood serum increased in both intervention groups, whereas only changes from the MCI group became statistically significant. Consistent with the results of our study, Behrendt et al showed that both open and closed skill exercises were equally efficient in acutely increasing the IL-6 serum levels in healthy older adults (Behrendt et al, 2021 ). However, Forti et al ( 2014 ) showed results, contrary to ours, that IL-6 levels significantly decreased after 12 weeks of strength training in 20 older adults.…”
Section: Discussionsupporting
confidence: 92%
“…BDNF is produced in the brain, muscle and hematological system in humans. Current human studies mainly observe the increased level of peripheral BDNF after exercise [ 69 , 70 ], which may be released from the muscle. In animal studies, increased BDNF content and mRNA have been detected in the hippocampus after exercise.…”
Section: Exercise Enhances Brain Plasticitymentioning
confidence: 99%
“…While a positive relationship between IGF-1 and hippocampus-dependent memory changes has been reported [56], this effect was independent of exercise, as aerobic fitness regimes did not increase the levels of the growth factor. In another study, it was reported that acute, rather than chronic, exercise led to higher peripheral IGF-1 levels [57]. However, it must be noted that, while in the acute regimen, samples were taken immediately after exercise, in the chronic group, sampling was done within a day.…”
Section: Boosting Igf-1 Towards Increasing Healthspanmentioning
confidence: 99%